Generation of linking social capital through microfinance cooperative the case of the Northern Samar Cooperative - Pormento, Nikki P. (2018)
Building social connection among citizens is achievable with the help of some development interventions like microfinance (Feigenberg, et al. 2010; Rankin, 2002). But forming social capital between government employees citizens can be challenging especially in areas where citizens are more inclined to forming bonds with neighbors than people of authority. This paper aims to determine how a microfinance cooperative can generate linking social capital between public can private stakeholders. An agriculture-based multi-purpose cooperative in Northern Samar in the Philippines that offers microfinance services to farmers is the focus of the research. It was successful in forming social capital between the Department of Agriculture (DA) employees and local farmers who availed of their microfinance services. Thematic case study analysis was used. data was gathered through sic in-depth interviews of farmers and cooperative officers. The study shows that social capital was generated through the trust and reciprocity practiced by private and public stakeholders in their cooperative. The trust is build through consistent interactions, increase of microcredit funds offered to farmers, provision of training and farm inputs to farmers by cooperative officers and Department of Agriculture employees, while norms of reciprocity are expressed through the sharing of information on farm techniques and inputs, respect for DA employees and cooperation in cooperative activities.
Keywords: Microfinance -- Northern Samar; Small business finance; Consumer cooperatives -- Northern Samar; Cooperative agriculture finance; Agricultural Workers and Entrepreneurs Multi-Purpose Cooperative (AWEMPC)